A sociological study of patterns and determinants of farmer suicide in India. Issue 3 (21st April 2022) - Kumar, Sumant; Sahoo, Barsa Priyadarsinee; Patel, Avanish Bhai
Abstract : Purpose: Farmer suicide as a social issue has existed in India since past three decades. Though many studies have been conducted from different perspectives to understand the causes and consequences of farmer suicide, very few studies have looked at the issue from a multidimensional perspective. By using the Durkheimian view of suicide, this paper aims to analyse the subjective meaning behind the social fact of suicide. It accesses the nature and pattern of suicide and examines the determinants of suicide from a socio-ecological paradigm. Design/methodology/approach: The present study mostly relies on National Crime Records Bureau (NCRB) data on "accidental deaths and suicide in India" for the year 2018, 2019 and 2020 for the analysis of pattern and determinants of farmer suicide in India. The analysis of the data has been done in Excel, and descriptive statistics have been presented through simple contingency table. Findings: The study found that in the past ten years, there has been a steady decline in the number of farmer suicide in India; however, some states such as Maharashtra and Karnataka continue to report high incidence of farmer suicide. Using a socio-ecological paradigm, the paper found that the farmer's social system which is constituted of individual characteristics and societal characteristics has a direct impact on the tendency of a farmer to commit suicide. It was observed that the stronger the relationship between an individual and its microsystem, there is less chance of a person to commit suicide. Originality/value: This is an original paper based on NCRB data for the year 2018, 2019 and 2020. The data for the farmer suicide has been calculated including the suicide of the agricultural labourers and the farmers/the cultivators.